Synthesis and characterization of amide linked triazolyl glycolipids as molecular hydrogelators and organogelators. Issue 65 (22nd August 2017) - Wang, Guijun; Chen, Anji; Mangunuru, Hari P. R.; Yerabolu, Jayasudhan Reddy
Abstract : Eighteen new glycolipids were synthesized and characterized. All eighteen are effective molecular gelators for at least one solvent and eleven are hydrogelators at concentrations of 0.15–1.0 wt%. The hydrogels are suitable carriers for sustained release of chloramphenicol. Abstract : Carbohydrate based small molecular gelators are important classes of compounds which can form useful soft materials with many practical applications. Although many different types of effective gelators have been reported, the rational design of a molecular hydrogelator is still challenging. In this research, we combined the structural features of two classes of monosaccharide based molecular gelators and obtained a new class of glycolipids that can function as molecular gelators. These new compounds were synthesized by introducing a triazole functional group to a protected 2-glucosamine through Cu(i ) catalyzed azide/alkyne cycloaddition reaction (CuAAC). A series of eighteen new glycolipids containing 4, 6- O -benzylidene acetal protectedd -glucosamide and triazole were synthesized and characterized. The self-assembling properties of these compounds were screened in several organic solvents, aqueous solutions, and water. All eighteen compounds are effective molecular gelators for at least one solvent and, more significantly, eleven compounds are hydrogelators with minimum gelation concentrations of 0.15–1.0 wt%. The hydrogels are suitable carriers for sustained release of chloramphenicol, and for the entrapment of toluidine blue dye. These results indicate that thed -glucosamide triazoles are effective templates for small molecular hydrogelators and are useful in designing sugar based soft materials.